2015
DOI: 10.1186/s12955-015-0218-4
|View full text |Cite
|
Sign up to set email alerts
|

The validity of the Child Health Utility instrument (CHU9D) as a routine outcome measure for use in child and adolescent mental health services

Abstract: BackgroundFew cost-utility studies of child and adolescent mental health services (CAMHS) use quality adjusted life years (a combination of utility weights and time in health state) as the outcome to enable comparison across disparate programs and modalities. Part of the solution to this problem involves embedding preference-based health-related quality of life (PBHRQOL) utility instruments, which generate utility weights, in clinical practice and research. The Child Health Utility (CHU9D) is a generic PBHRQOL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
82
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 44 publications
(60 reference statements)
10
82
2
Order By: Relevance
“…Because the recall period (one day) is so short, the measure may be insensitive to issues that irregularly affect respondents. For example, a recent study investigating the measure's use in children receiving mental health services found that asking about today may have underestimated estimations of dysfunction because today was atypical in some way [28]. As relates to the INCLUSIVE trial, the CHU-9D may minimise estimated differences in HRQol related to bullying victimisation and school antisocial/aggressive behaviour since these behaviours often do not occur on a daily basis.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the recall period (one day) is so short, the measure may be insensitive to issues that irregularly affect respondents. For example, a recent study investigating the measure's use in children receiving mental health services found that asking about today may have underestimated estimations of dysfunction because today was atypical in some way [28]. As relates to the INCLUSIVE trial, the CHU-9D may minimise estimated differences in HRQol related to bullying victimisation and school antisocial/aggressive behaviour since these behaviours often do not occur on a daily basis.…”
Section: Limitationsmentioning
confidence: 99%
“…Refining the CHU-9D's recall period to "a typical day" as suggested by Furber and Segal may alleviate this issue [28]. The recall period for the PedsQL is longer at one month and potentially this could lead to different findings.…”
Section: Limitationsmentioning
confidence: 99%
“…Evaluating patient safety and quality interventions in health care have traditionally focused on health system outcomes such as mortality and morbidity. Assessing broader measures of the impact on patients can be challenging in children as patient‐reported quality‐of‐life measures that are used in adult studies are often not validated in younger age groups . Paediatric care is also complicated by the impact of a child's illness on the family as parents are encouraged to actively participate in their child's care when in hospital, and a child's admission involves the whole family as parents juggle jobs and other care commitments .…”
mentioning
confidence: 99%
“…The recall period is today/last night. The CHU9D has demonstrated validity in paediatric clinical populations [52]Communication questionnaireA short questionnaire developed specifically for this study will be used to explore children’s perceptions of the communication around physical activity they have with their diabetes team. It contains two items and assesses children’s perceptions of (1) frequency of physical activity discussion (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…The recall period is today/last night. The CHU9D has demonstrated validity in paediatric clinical populations [52]…”
Section: Methodsmentioning
confidence: 99%